Impact of pretransplant vitamin D deficiency on immune recovery and clinical outcomes in multiple myeloma patients undergoing autologous stem cell transplantation - Keruakous, Amany R.; Ghani, Nabil; Desai, Shreya; Terrell, Christopher; Zamani, Shahrzad; Youn, Linda; Iska, Sindu; Keruakous, Mai; Cui, Zhu (Frontiers in Immunology, 2025)
This study examines the impact of pretransplant vitamin D deficiency on immune recovery and clinical outcomes in multiple myeloma patients undergoing autologous stem cell transplantation (ASCT). Given vitamin D’s known immunomodulatory effects, the research describes its influence on neutrophil and platelet engraftment, lymphocyte recovery, and overall response rates post-ASCT. By analyzing a retrospective cohort, the study highlights potential associations between vitamin D status and post-transplant immune reconstitution, contributing to understanding vitamin D’s role in optimizing treatment strategies for multiple myeloma patients. Multiple myeloma (MM), considered the second most common hematological malignancy, is a plasma cell neoplasm that causes morbidity and mortality through its effects on organs, organ systems, and immunity. Clinical manifestations of MM include renal dysfunction, hypercalcemia, osteolytic bone lesions, anemia (CRAB Criteria), pathological fractures, and immunosuppression. The majority of myeloma patients suffer from long-term immunoparesis, which means suppression of uninvolved immunoglobulins (Igs), and these findings have been reported to be associated with poor prognosis in patients with multiple myeloma (MM).